Spatiotemporal regulation of target mRNA cleavage by 21-nt phasiRNAs in maize anthers - Bi Lian; Tianxiao Huang; Wei Huang; Pengfei Jiang; Weiwei Jin; Yijun Qi (Proceedings of the National Academy of Sciences, 2025)
21-nt phasiRNAs are abundantly expressed in anthers and play crucial roles in anther development and male reproduction in grasses. In maize, the target genes that 21-nt phasiRNAs regulate remain largely unknown. Here, we show that 21-nt phasiRNAs direct the cleavage of hundreds of target mRNAs in maize. Interestingly, while 21-nt phasiRNAs in anthers (somatic anther wall cells) do not have obvious preference for a particular nucleotide at the 5′ end and target genes implicated in stress response and cellular homeostasis, 21-nt phasiRNAs in male germ cells preferentially initiate with 5′ C and target genes related to meiotic processes in a ZmAGO5c-dependent manner. Our results indicate that mRNA cleavage is a conserved mechanism used by 21-nt phasiRNAs for gene regulation in grasses. However, the sequences of 21-nt phasiRNAs and their targets show little conservation in maize and rice, suggesting that 21PHAS loci and 21-nt phasiRNA targets have undergone fast divergence in grasses.